Emergency Remote Teaching and the Black Swan Logic (Research, Society and Development, 2021)
The Black Swan Logic is important for the present moment because of the lessons assumed by the author, risk analyst and mathematician Nassim Nicholas Taleb. The Black Swan Logic has as a principle, the fragility of knowledge through learning from observations and experiences. The Black Swan is an event characterized by the triad: rarity, extreme impact and retrospective predictability, elements present in the current moment. The article aims to expose the strategies applied in the engineering undergraduate course for remote emergency teaching of the Topics in Alternative Energy Sources (TAES) discipline, in the context of the COVID-19 pandemic, permeated by lessons from the Black Swan Logic. Experiences on the exceptionality of the modus operandi of the TAES discipline, which is part of the last period of the electrical engineering course curriculum and an optional requirement for access to the postgraduate program offered by the institution, are reported. Institutional strategies as well as specific methodologies and strategies proposed for the ministry of TAES are discussed. Effective student participation and a consistent evaluation model are among the results achieved that consolidate the permanent need for innovation in search of pedagogical adjustments, reinventing conservative models, a lesson advocated in the Black Swan Logic. Finally, the evolution of digital transformation and the importance of the digital mindset will lead to a future advanced hybrid model for post-pandemic higher education.